Introduction to Tabriz Historic Bazaar Complex as One of the UNESCO World Heritage Sites in Iran - Narmin Babazadeh Asbagh (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Tabriz is one of the ancient cities in the northwest of Iran that has suffered from natural disasters like severe earthquakes and floods throughout history. Tabriz Historic Bazaar Complex is one of the UNESCO World Heritage Sites in Iran, the biggest covered bazaar worldwide. This historic complex has faced several earthquakes, floods, and fire accidents, but has survived each time and still serves as the most important commercial part of the city. This article aims to introduce this UNESCO World Heritage Site internationally for the preservation of this significant complex in Tabriz. After brief research about Tabriz, the Tabriz Historic Bazaar Complex is introduced comprehensively. This historical research is based on a qualitative method and personal observations of the author. The results of this article can be useful for preservationists and conservationists in the field of cultural heritage, architects, interior designers, and urban planners of ancient cities.